COINS OF EARLY MEDIEVAL KHWARAZM - Rustam A.Nematov (Journal of Learning on History and Social Sciences, 2024)
The paper briefly analyzes the coins minted by the Khwarazm oasis rulers during the period of the Turkic Khaganate. And through these studies, the coins minted in the Khwarazm oasis provide an opportunity to determine the socio-political and ethnocultural situation of their time, as well as to determine the names of the rulers of Khwarazm, and to more accurately restore the names of the Khwarazmshah-Afrighits known through written sources